Morphometric Characteristics, Length–Weight Relationship, and Condition Factor of Kapis Clams (Pecten maximus, Linnaeus, 1758) in Sarang Island Coastal Waters - Khoirotunnisa Siregar; Ramses Ramses; Lani Puspita; Ismarti Ismarti (Universitas Labuhanbatu, 2026)
Background: This study examined the morphometric characteristics, length–weight relationship, and condition factor of scallops belonging to the family Pectinidae in the waters of Sarang Island and Mecan Island, Belakang Padang District, Batam City. This research is important because scientific information regarding the biological characteristics and population condition of scallops in this area is still limited, while exploitation by local fishermen continues to occur. Methodology: The study was conducted from August to October 2024 using a quantitative descriptive approach. Sampling was carried out through diving surveys at three fishing stations using a sweeping technique along transects covering an area of approximately 100 m² at depths ranging from 2–6 m. Morphometric measurements included shell length, shell width, shell thickness, dorsal width, and total body weight. The length–weight relationship was analyzed using logarithmic regression, while physiological condition was evaluated using the relative condition factor (Kn). Findings: A total of 88 individuals were collected.. Water quality parameters showed suitable environmental conditions with temperature ranging from 29–31 °C, salinity 30–32 ppt, dissolved oxygen 5.2–6.4 mg/L, and pH 7.6–8.1. The growth exponent (b = 2.5877) indicates a negative allometric growth pattern, where shell length increases faster than body weight. This pattern may reflect ecological adaptation and environmental conditions in the study area. Contributions: These findings provide baseline biological information for sustainable scallop resource management